Pengaruh Literasi Keuangan, Inklusi Keuangan, Dan Modal Usaha Terhadap Keberlanjutan Usaha Mikro, Kecil Dan Menengah (UMKM) Di Kabupaten Karangasem - Ni Nyoman Ari Wahyuni; I Putu Deddy Samtika Putra; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2025)
The l sustainability of MSMEl s is ve l ry important for improving the l e l conomy of a re l gion, so it is important for MSMEl busine l ss actors to be l able l to unde l rstand the l factors that can support the l sustainability of MSMEl s, one l of which is financial lite l racy, financial inclusion and the l influe l nce l of busine l ss capital. This re l se l arch has a proble l m formulation of how financial lite l racy, financial inclusion and busine l ss capital influe l nce l the l sustainability of MSMEl s in Karangase l m Re l ge l ncy. The l aim of this re l se l arch is to de l te l rmine l the l influe l nce l of financial lite l racy, financial inclusion and busine l ss capital on the l sustainability of MSMEl s in Karangase l m Re l ge l ncy. The l population in this study was 50,717 MSMEl s in Karangase l m from 2021 - 2023 with a sample l size l of 100 re l sponde l nts. The l data colle l ction me l thod in this re l se l arch is a que l stionnaire l te l chnique l . The l data analysis te l chnique l s use l d in this re l se l arch are l multiple l line l ar re l gre l ssion analysis, coe l fficie l nt of de l te l rmination te l st, and t te l st. The l re l sults obtaine l d in this re l se l arch are l 1) financial lite l racy has a positive l and significant e l ffe l ct on the l sustainability variable l of MSMEl s, so that the l first hypothe l sis (H1) is acce l pte l d se l e l ing that the l parame l te l r coe l fficie l nt is 0.395 and the l t-calculate l d value l is 4.905, with a significance l le l ve l l of 0.000. 2) financial inclusion has a positive l and significant e l ffe l ct on the l sustainability variable l of MSMEl s, so that the l se l cond hypothe l sis (H2) is acce l pte l d conside l ring the l parame l te l r coe l fficie l nt value l is 0.354 and shows a t-calculate l d value l of 2.662 with a significance l le l ve l l of 0.000. 3) busine l ss capital has a positive l and significant e l ffe l ct on the l sustainability of MSMEl s, so that the l third hypothe l sis (H3) is acce l pte l d se l e l ing that the l parame l te l r coe l fficie l nt value l is 0.100 and shows a t-count value l of 1.993 with a significance l le l ve l l of 0.049. The l sugge l stion in this re l se l arch is that MSMEl playe l rs can use l the l Si Apik application as a digital financial re l cording application which can make l it e l asie l r for MSMEl s to re l cord financial transactions and furthe l r re l se l arch can add othe l r variable l s that can influe l nce l the l sustainability of MSMEl s in Karangase l m Re l ge l ncy.